The Extracellular Matrix Glycoprotein Tenascin C and Adult Neurogenesis - Tucić, Milena; Stamenković, Vera; Andjus, Pavle (Frontiers in Cell and Developmental Biology, 2021)
Tenascin C (TnC) is a glycoprotein highly expressed in the extracellular matrix (ECM) during development and in the adult central nervous system in regions of active neurogenesis, where neuron development is a tightly regulated process orchestrated by extracellular matrix components. In addition, newborn cells also communicate with glial cells, astrocytes and microglia, indicating the importance of signal integration in adult neurogenesis. Although TnC has been recognized as an important molecule in the regulation of cell proliferation and migration, complete regulatory pathways still need to be elucidated. In this review we discuss the formation of new neurons in the adult hippocampus and the olfactory system with specific reference to TnC and its regulating functions in this process. Better understanding of the ECM signaling in the niche of the adult central nervous system will have significant implications for regenerative therapies.